2008
DOI: 10.1590/s0103-21002008000200002
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de portadores de insuficiência cardíaca

Abstract: OBJETIVO: Identificar o nível de qualidade de vida de portadores de insuficiência cardíaca; o grau de insuficiência cardíaca dos pacientes; a opinião dos portadores de insuficiência cardíaca quanto ao seu estado de saúde atual quanto comparada há um ano atrás. MÉTODOS: A amostra foi composta por 30 portadores de insuficiência cardíaca atendidos em ambulatório de um hospital geral e público do município de Taboão da Serra - SP. Para a coleta de dados foi utilizado o Medical Outcomes Study 36-item Short Form Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
(25 reference statements)
0
12
0
14
Order By: Relevance
“…[21][22][23][24][25][26] *LVEF = left ventricular ejection fraction; † missing data = 4; ‡ missing data = 2; NYHA = New York Heart Association assesment. SF-36 reliability was evaluated in terms of internal consistency using Cronbach's alpha coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[21][22][23][24][25][26] *LVEF = left ventricular ejection fraction; † missing data = 4; ‡ missing data = 2; NYHA = New York Heart Association assesment. SF-36 reliability was evaluated in terms of internal consistency using Cronbach's alpha coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a study carried out on a younger population has indicated not only physical impairment but also emotional impairment. 23 Other studies [24][25][26] on elderly populations suffering from different chronic diseases have described physical functioning and role-physical as the HRQoL dimensions most affected. In a recent study on a sample of 1958 Brazilian elderly individuals, Lima et al 29 observed significant social inequality in HRQoL, especially in relation to physical functioning and physical role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study were similar to those found by other investigations, whose individuals presented higher scores in the physical dimension compared to the emotional one (7,12) . A study carried out with the elderly population, using the generic instrument SF-36, observed that the dimensions that assessed the physical aspects were more affected (25) . Patients with HF change their lifestyle because they cannot do some tasks due to dyspnea, fatigue and edema (26) .…”
Section: Discussionmentioning
confidence: 99%